Prioritizing multiple therapeutic targets in parallel using automated DNA-encoded library screening - Carl A. Machutta (Nature Portfolio, 2017)
Encoded Library Technology (ELT) has streamlined the identification of chemical ligands for protein targets in drug discovery. Here, the authors optimize the ELT approach to screen multiple proteins in parallel and identify promising targets and antibacterial compounds forS. aureus, A. baumannii and M. tuberculosis.